An investigation of the effects of thiamine in the experimental diabetic rat brain tissue - Akalin, Yahya; Bulut, Serpil; Kuloglu, Tuncay; Demir, Caner F.; Tasci, Irem (Edizioni Minerva Medica, 2020)
BACKGROUND: Thiamine is necessary in the catabolism of carbohydrates and most amino acids. In experimental studies, it was observed that thiamine has antioxidant properties. In this study, the protective effects of thiamine were investigated on the apoptotic changes of brain tissue in a diabetic rat model induced by streptozotocin. METHODS: Twenty-one adult male Wistar albino rats were divided into three groups (N.=7 each). Group I was used as control. Rats in group II (DM) and group III (DM-T) were exposed intraperitoneal streptozotocin (50 mg/kg) to establish diabetes mellitus rat model. After confirmed of experimental diabetes mellitus, diabetic animals in DM group were received just standard chow and water, whereas diabetic rats of DM-T group were received thiamine (25 mg/kg/day, oral) for six weeks. After treatment duration, all of rats were decapitated. To observe the apoptotic changes TUNEL and immunohistochemical (Bax) techniques were used. malondialdehyde (MA) levels were measured in brain tissue. RESULTS: In immunohistochemistry and TUNEL staining; according to the group I and group III Bax immunoreactivity and apoptotic cells were increased in group II. MDA levels increased significantly in DM group compared to group I, also reduced significantly DM group compared DM-T. CONCLUSIONS: It was observed that thiamine has protective effects against DM induced apoptotic changes in the brain tissues. To prevent DM induced cerebral complications, thiamine treatment may be useful.
Keywords: Thiamine; Diabetes mellitus; Apoptosis; Malondialdehyde